Design of robust fractional order PID controllers for coupled tank systems using multi-objective particle swarm optimisation. (2017) - Katal, Nitish; Narayan, Shiv
Liquid level control in multiple connected tanks is a nonlinear control problem and is centre to various diverse industrial establishments, especially chemical process industries. The quality of products and process safety greatly relies upon the quality of control. In this paper, robust liquid level control for coupled tank systems has been proposed using optimal fractional order PID controllers. The controller tuning has been posed as multi-objective mixed sensitivity minimisation problem and is solved using multi-objective variant of particle swarm optimisation (MOPSO). At the end of the optimisation process, Pareto optimal set (POS) of solutions has been obtained. For choosing an optimal solution from the POS, there are several graphical methods like Pareto front, scatter matrices, parallel coordinate representations, etc. But these methods offer a very compact representation of the data and the problem arises for m-dimensional problems. So to ease the decision-making process, the paper also explores the use of level diagrams for aiding the decision maker in choosing the ideal solution from the Pareto optimal set. The designed fractional order PID controllers present robust behaviour to external disturbances and efficient tracking of the reference signal and the results obtained has been compared with different controller tuning algorithms.